2018
DOI: 10.3390/nu10010066
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Binge Eating Behavior among Malaysian Adolescents

Abstract: Although there are numerous studies on binge eating behavior in the Western countries, studies on this behavior in Malaysia are still limited. Therefore, this cross-sectional study aimed to determine the risk factors associated with binge eating behavior among adolescents in Malaysia. The study included 356 adolescents (42.7% males and 57.3% females), aged 13 to 16 years. They completed a self-administered questionnaire on demographic and socioeconomic backgrounds, frequency of family meals, family meal enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 51 publications
2
28
1
Order By: Relevance
“…In other words, all ethnic groups were at risk of DE in university students. Contrary to the several local studies, ethnicity was significantly associated with disordered eating in Malaysian children and adolescents [16,17,27]. It might imply that university students are more concerned about their body image compared to their younger counterparts that resulted in DE across the ethnic groups.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In other words, all ethnic groups were at risk of DE in university students. Contrary to the several local studies, ethnicity was significantly associated with disordered eating in Malaysian children and adolescents [16,17,27]. It might imply that university students are more concerned about their body image compared to their younger counterparts that resulted in DE across the ethnic groups.…”
Section: Discussionmentioning
confidence: 61%
“…A previous study conducted in Malaysia had found that the higher acceptances towards body image in female undergraduate Malaysian medical students were associated with higher susceptibility to eating disorders [41]. Body size dissatisfaction also predicted a higher risk of DE in urban females [42] and appears to contribute to binge eating behaviours among Malaysian adolescents [17]. In a sample of South-East Asian university students, it was found that students who perceived themselves as overweight had higher odds of DE when compared to students who had perceived themselves as having normal body weight [19].…”
Section: Discussionmentioning
confidence: 93%
“…Overeating is associated with higher levels of stress, anxiety and depression in a number of large-scale studies (e.g. Jung et al 2017;Lee-Winn et al 2016), while the association between binge eating and psychological distress is also clearly recognised (Elliot et al 2013;Gan et al 2018). Literature has evidenced the impact of depression, anxiety and stress, or "wellbeing" on overeating and binge eating and provides a clear rationale for controlling for these effects in any experimental studies in eating behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…The test–retest reliability and internal consistency of BES were 0.71 and 0.85, respectively (Mootabi et al, ). Also, the BES has been validated among adolescents (Cuzzocrea, Costa, Larcan, & Toffle, ; Gan, Mohamad, & Law, ).…”
Section: Methodsmentioning
confidence: 99%
“…The test-retest reliability and internal consistency of BES were 0.71 and 0.85, respectively (Mootabi et al, 2009). Also, the BES has been validated among adolescents (Cuzzocrea, Costa, Larcan, & Toffle, 2015;Gan, Mohamad, & Law, 2018). Informed consent was obtained from the school authorities before the commencement of this survey.…”
Section: Binge Eating Scalementioning
confidence: 99%